Analysis of Multiple-Bit Shift-Left Operations on Complex Numbers in (−1+j)-Base Binary Format - Tariq Jamil; Usman Ali (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Complex numbers find various applications in the field of engineering. To avoid excessive delays in production of results obtained by implementing divide-and-conquer technique in dealing with arithmetic operations involving this type of numbers in today’s computer systems, Complex Binary Number System with base(−1+j) has been proposed in scientific literature. In this paper, we have investigated the effects of bit-wise shift left operations (from 1-8 bits) on the complex binary representation of complex numbers and analyzed these results using mathematical equations.DOI:http://dx.doi.org/10.11591/ijece.v4i2.5283